Social contextual factors, social support and accessibility of social services in the health and life satisfaction of family caregivers in Hong Kong - Shaolingyun Guo; Qiqi Chen; Ko Ling Chan (BMC Public Health)
Abstract Purpose Health issues and life satisfaction among family caregivers have attracted significant public and scholarly attention, but research on socio-demographic and social contextual factors contributing to family caregivers’ burdens remains limited in scope. This study aims to assess the factors associated with subjective health, mental health and life satisfaction among family caregivers based on a representative community sample of Hong Kong families. Methods The analysis was performed using the Family Survey, a territory-wide household survey conducted in Hong Kong. The data for the current study included 1,647 family members in either nuclear families or extended households. A three-phase multivariate regression analysis was carried out to investigate the associations between a variety of social contextual factors and physical health, mental health, as well as life satisfaction. Results Results show that female caregivers experience significant psychological health burdens, older caregivers face physical health burdens, unemployment impacts overall life satisfaction, and lower monthly income and smaller living spaces contribute significantly to physical health and life satisfaction. Additionally, primary caregiving roles are associated with lower life satisfaction, while a higher level of perceived social support leads to better health and a higher level of life satisfaction. No significant relationship was found between caregiving duties and constraints on accessing social services for assistance. Conclusion The study highlights the importance of enhancing social support and economic assistance for caregivers, particularly for women and the elderly, to alleviate psychological and physical burdens. Future services should focus on improving accessibility to social service resources and developing targeted programs to address these specific needs.